2021
DOI: 10.1002/ejoc.202100866
|View full text |Cite
|
Sign up to set email alerts
|

Chroman‐4‐one‐Based Amino Bidentate Ligand: An Efficient Ligand for Suzuki‐Miyaura and Mizoroki‐Heck Coupling Reactions in Aqueous Medium

Abstract: A new family of phosphine-free Amino-chroman-4-one ((Z)-2ethoxy-3-((phenylamino)methylene)chroman-4-one) bidentate ligands ware successfully synthesised and characterised. The bidentate ligand act as efficient catalyst with combination of Pd (II) salt in the CÀ C bond formation and exhibited excellent performance in the Suzuki-Miyaura and Mizoroki-Heck coupling reaction. A broad range of substrates, including heterocyclic, flavones, Isatin and sterically hindered coupling partner, were well tolerated under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…To confirm the metal-ligand complex, we performed a controlled experiment with the ligand A1 and PdCl 2 ratio (1 : 1) in i-PrOH at 70 °C for 5 minutes under microwave irradiation (Scheme 6). The formation of the metal-ligand complex was confirmed by 1 Based on the literature [19,33,34] and the palladium (II) complex (B) as confirmed in Scheme 6, possible catalytic cycles for Suzuki-Miyaura and Mizoriki-Heck coupling reactions are shown in Schemes 7 and 8, respectively. The complex (B) is reduced to palladium ( 0 Based on the literature, [35] intermediate (D) was formed by the oxidative addition of bromobenzene (4 b).…”
Section: Control Experiments For Mechanistic Studymentioning
confidence: 87%
See 4 more Smart Citations
“…To confirm the metal-ligand complex, we performed a controlled experiment with the ligand A1 and PdCl 2 ratio (1 : 1) in i-PrOH at 70 °C for 5 minutes under microwave irradiation (Scheme 6). The formation of the metal-ligand complex was confirmed by 1 Based on the literature [19,33,34] and the palladium (II) complex (B) as confirmed in Scheme 6, possible catalytic cycles for Suzuki-Miyaura and Mizoriki-Heck coupling reactions are shown in Schemes 7 and 8, respectively. The complex (B) is reduced to palladium ( 0 Based on the literature, [35] intermediate (D) was formed by the oxidative addition of bromobenzene (4 b).…”
Section: Control Experiments For Mechanistic Studymentioning
confidence: 87%
“…Several bases including Na 2 CO 3 , Cs 2 CO 3 , K 3 PO 4 , KOH, NaOAc, KOAc, KOEt, KOt-Bu, Et 3 N and piperidine (Table 3, entries 4-13) were examined and KOt-Bu was found to be the most suitable, giving product 13 a in 82% yield in isopropanol (Table 3, entry 11). A study of various solvents such as H 2 O, EtOH, t BuOH, DMF, DMSO and THF (Table 3, entry [14][15][16][17][18][19][20] showed that solvents such as t BuOH were more efficient and produced the maximum amount of product 13 a in 90% yield (Table 3, entry 17).…”
Section: Microwave Assisted Buchwald-hartwig Reactionmentioning
confidence: 99%
See 3 more Smart Citations